(untitled) (Global Journal of Advanced Engineering Technologies and Sciences, 2020)
Nanofluids are a new generation of heat transfer fluids is an emerging area of research. Because of their superior thermophysical properties, researchers have been attracted to their application in various thermal devices. Researchers have indicated that the positive impact of the application of nanofluids on thermal performance is due to their improved thermal properties such as thermal conductivity, specific heat, viscosity, etc. The application of nanofluids in a variety of thermal devices has been shown to have a positive impact on thermal performance. This paper summarizes recent advances in the study of nanofluids, such as preparation methods, synthesis of the thermo-physical properties of nanofluids, and factors that influence its thermophysical properties were discussed. All these parameters have distinct or combined effects on the thermophysical properties of nanofluids.